Standardization of detached leaf assay to screen chickpeas for resistance to beet armyworm, Spodoptera exigua (Hübner, 1808) - Shankar MARLABEEDU; Suraj Prasad MISHRA; Hari Chanda SHARMA; Jagadish JABA; Ramesh Babu TATINENI; Ramesh Babu TATINENI; Sridevi DASARI (Acta Agriculturae Slovenica)
The beet armyworm, Spodoptera exigua (Hübner, 1808) is an important pest of several economically important crops, and recently emerged as a serious pest of chickpea in South Central India. We standardized a detached leaf assay technique to evaluate chickpea germplasm and segregating populations for resistance to this pest under laboratory conditions. Two chickpea genotypes ICCL 86111 and ICC 3137 grown under field and greenhouse conditions were used for the detached leaf assay at the vegetative and flowering stages. The terminal branches were infested with 5, 10, 15, and 20 neonate larvae of S. exigua. The test genotypes were also infested with 2, 4, 6 and 8 third-instar larvae at the podding stage. At the vegetative stage, ICCL 86111 suffered less damage than ICC 3137 across infestation levels. The differences in larval survival between the genotypes were significant, and larval survival was lower on ICCL 86111 than on ICC 3137 across infestation levels. The results suggested that infesting the chickpea terminal branches with 10–15 neonate larvae per branch at the vegetative stage or six third-instar larvae at the podding stage can be used to evaluate chickpea genotypes for resistance to S. exigua.